The Role of the Fund in Governance Issues : Review of the Guidance Note. (Policy Papers; Policy Paper, 2017)
Following the request of the IMFC, this paper represents a first step in reassessing the Fund's approach to tackling governance issues, the guidelines for which are contained in a 1997 Guidance Note. The paper examines the record of implementation of these guidelines in the period since the last such review was conducted in 2004, focusing on the handling of issues relating to corruption.